Evaluation of structured doctoral training programs in German life sciences: how much do such programs address hurdles faced by doctoral candidates? - Meuleners, Julia S.; Boone, William J.; Fischer, Martin R.; Neuhaus, Birgit J.; Eberle, Julia (Frontiers in Education, 2023)
Ways to improve the quality of doctoral education are debated internationally. In Europe, the United States, and other countries, there have been policy initiatives to address these. One approach has been the implementation of so-called structured doctoral training programs (doctoral programs) including formal structures such as courses, supervision agreements, external examiners for grading the thesis. However, there is little known about how doctoral programs implement the debated structures. As a result, the question arises whether existing programs already address the challenges of doctoral education and implement policy demands. In this study, we evaluated the structure of 82 life science doctoral programs in Germany. We focused on their (1) interdisciplinary aspects and (2) the international orientation of these programs. We evaluated the (3) courses offered, (4) formal characteristics of supervision to avoid over-dependence of doctoral candidates on the goodwill of supervisors, and (5) examination regulations concerning counteracting potential conflicts of interest. The results showed that the doctoral programs already address these five aspects to some extent. However, there is variability as a function of institution and details of policy demand realizations are very heterogeneous. Some doctoral programs provide opportunities for interdisciplinary cooperation, but only few promote international orientation. Offered courses cover some relevant academic skills, but courses on e.g. teaching, open access and public outreach are still rare. Structured regulations on supervision, e.g. through regular meetings and supervision agreements, are also rarely implemented. Lastly, most supervisors remain strongly involved in examining doctoral theses. We conclude that there is still a crucial need for improvement of doctoral programs through more extensive implementation of policy demands. We detail cross-national and -disciplinary practical implications for coordinators of doctoral programs.